Demonstration of a kW-scale solid oxide fuel cell-calciner for power generation and production of calcined materials - Nabavi, Seyed Ali; Erans, María; Manovic, Vasilije (Elsevier, 2019)
Carbonate looping (CaL) has been shown to be less energy-intensive when compared to mature carbon capture technologies. Further reduction in the efficiency penalties can be achieved by employing a more efficient source of heat for the calcination process, instead of oxy-fuel combustion. In this study, a kW-scale solid oxide fuel cell (SOFC)-integrated calciner was designed and developed to evaluate the technical feasibility of simultaneously generating power and driving the calcination process using the high-grade heat of the anode off-gas. Such a system can be integrated with CaL systems, or employed as a negative-emission technology, where the calcines are used to capture CO2 from the atmosphere. The demonstration unit consisted of a planar SOFC stack, operating at 750 °C, and a combined afterburner/calciner to combust hydrogen slip from the anode off-gas, and thermally decompose magnesite, dolomite, and limestone. The demonstrator generated up to 2 kWel,DC power, achieved a temperature in the range of 530–550 °C at the inlet of the afterburner, and up to 678 °C in the calciner, which was sufficient to demonstrate full calcination of magnesite, and partial calcination of dolomite. However, in order to achieve the temperature required for calcination of limestone, further scale-up and heat integration are needed. These results confirmed technical feasibility of the SOFC-calciner concept for production of calcined materials either for the market or for direct air capture (DAC).
Keywords: Solid oxide fuel cell; SOFC-calciner; Power generation; Calcination; Direct air capture; Negative emission